THE QUALITY OF BIOLOGY TEXTBOOK BASED ON CURRICULUM 2013 FOR SENIOR HIGH SCHOOL CLASS X PUBLISHED BY ERLANGGA; PERCEPTION OF BIOLOGY TEACHERS AND STUDENTS IN PEKANBARU - Darmadi ' '; Mariani Natalina ,; Suci Indah Permata Sari (Program Studi Pendidikan Biologi, 2015)
The purpose of this study was determine the perception of Biology teachers and Public Senior High School students in Pekanbaru to the quality of Biology textbook based on Curriculum 2013for Senior High School class X published by Erlangga. This study was conducted from January to June 2014. Sample in this study were 6 Biology teachers who taught in class X and 274 Public Senior High School students class X majors MIA (Matematika dan Ilmu Alam) in Pekanbaru who became target the implementation of Curriculum 2013. Data collection instruments was questionnaires, which grouped into teacher questionnaire and student questionnaire. Teacher questionnaire consists of the closed-ended questionnaire was 50 statments and divided into 5 indicators, the indicators are feasibility content, material presentation, language, book graph, and compatibility with Curriculum 2013. The open-ended questionnaire was 5 questions. Student questionnaire consists of the closed-ended questionnaire was 26 statments divided into 4 indicators, the indicators are feasibility content, material presentation, language, and book graph. Data analyzed descriptively. Overall, the quality of Biology textbook based on Biology teachers perception showed in quite well criteria with average of 2,54 and based on students perception showed quite well criteria with average 2,43. This indicate the textbook have not been able to complete all criteria that has been established by BSNP (Badan Standar Nasional Pendidikan).Keywords : Perception, Quality of Biology Textbook, Curriculum 2013